(untitled) (El-Wahat Journal for Research and Studies, 2025)
Academic writing involves both linguistic and self-regulatory skills, namely cognitive strategies that students need to deploy in performance. This study investigates the type of relationship(s) existing between cognitive/metacognitive self-regulatory strategy use on the one hand and academic writing performance on the other hand. The study sample is Master 1 students (N=82) of Language Sciences at Badji Mokhtar University of Annaba. Data tools consist of a self-report questionnaire in addition to an index of performance based on exam scores (2022/2023). Data were analysed by means of a correlational analysis, using T-test and simple linear regression. Findings revealed a moderate positive association (R2= 0.514) between the study variables with an effect of (b=0.420). Participants’ use of cognitive strategies was found to affect performance by 51.4 %. Recommendations were provided to hone students’ writing performance within a self-regulatory perspective. Keywords: Academic writing performance,Self-regulatory skills,Cognitive and metacognitive strategies , Masters 1 students of English , Correlation